SOUND AS MEDICINE FOR MENTAL AND EMOTIONAL WELLNESS - Dr. Sujata Singhi (International Engineering Journal For Research & Development, 2021)
Depression, stress, overthinking, and anxiety are associated with a higher risk of disease. This study has looked into the effects of sound therapy, the Himalayan Singing Bowl, on mental and emotional wellness. 51 members participated with a mean age of 45.2 years. In following the Himalayan Sound Therapy, the individuals reported reduced anxiety, lower stress, lessened anger, and an increase in emotional well-being (Ps <.001) compared to their earlier life. Feeling of emotional wellness, mental health, focus, and memory significantly improved across all the individuals (Ps <.001). When used as a therapeutic solution for improving emotional wellness and mental health, the Himalayan singing bowl may facilitate faster relaxation and release of stress when compared to simple relaxation techniques. This singing bowl therapy may also be extensively beneficial for the younger generation with behavioural disorders in learning methods to handle their emotions and manage mental health. The scientific facts have established a connection between stress and other anxiety-related disorders through ways that impact the psyche and the body. Stress and anxiety also have a significant impact on the immune system of an individual. Anxiety harms the autonomic nervous system by hyper-activating the sensitive nervous system also acknowledged as a “fight or flight” mode. To handle the impact of stress on bodily processes, it is vital to turn on the “rest and absorb” mode, i.e., parasympathetic nervous system activity.Majority of the diseases like heart, diabetes, and mental diseases have all been associated with stress and anxiety. Meditation, together with mindfulness-based meditations, has shown assurance in inducing the relaxation reaction and aiding alleviates anxiety and enhances well-being. The relaxation response is the body’s physical response in relaxation, with lower blood pressure to defy the fight-or-flight response and start of the parasympathetic nervous system. As capable as alertness and other meditation systems, a frequent grumble is the time, persistence, and discipline necessary to learn meditation. Thus, a form of relaxation and strain relief that does not need a precipitous learning curve or an immense deal of obedience to utilize could potentially be a vast benefit to mental and emotional wellness.